Enhancement of photon–magnon coupling strength by inverted split-ring resonator at GHz - A. Girich; S. Nedukh; S. Polevoy; K. Sova; S. Tarapov; A. Vakula (AIP Advances, 2024)
A series of inverse split-ring resonators (ISRR) loaded with an yttrium iron garnet (YIG) film were numerically and experimentally studied to provide strong photon–magnon coupling strength and cooperativity enhancement. An increase in the photon–magnon coupling strength and cooperativity has been achieved due to the simultaneous increase in the spatial overlapping between the ISRR microwave electromagnetic field magnetic component and the uniform magnon mode in the YIG, and the appearance of spatial areas with higher ISRR electromagnetic field magnetic component strength. Practically, this was reached for the ISRR by increasing the conducting gap length and changing the conducting gap shape by protrusions forming. Higher values of spin-number-normalized photon–magnon coupling strength gN and cooperativity C were reached in all cases for the ISRR with protrusion (compared with ISSR with identical conducting gap length but without protrusion). All resonators presented in this paper seem to be more prospective for the realization in quantum hybrid systems than conventional split-ring resonators and ISRR.